ANTIBIOTIC RESISTANCE DURING WARTIME: NEW RISKS AND SPECIFIC PATTERNS OF DEVELOPMENT - Коваль, Галина; Карбованець, Олена (SWorldJournal, 2025)
The article addresses antibiotic resistance during wartime as one of the major challenges for healthcare systems. Armed conflicts are accompanied by a sharp increase in the number of wounded, severe combined injuries, extensive microbial contamination of